Bioética animal: antropocentrismo y otras reflexiones - Chaverri Suárez, Federico (2011)
This article covers different historic and philosophic conceptions that man has raised in regard to animals and their relationship with humankind. Finally, a critical analysis is drawn up regarding “humancenteredness” and “bio-centeredness” and a moderate stand is taken concerning these two theses.